Neurochemical impact of the 5-HT2C receptor agonist WAY-163909 on monoamine tissue content in the rat brain. (March 2019) - Chagraoui, Abdeslam; Whitestone, Sara; Baassiri, Lynn; Manem, Julien; Di Giovanni, Giuseppe; De Deurwaerdère, Philippe
Abstract: Serotonin2C receptor (5-HT2C ) agonists are promising drugs for the treatment of neuropsychiatric diseases. However, their effect is not completely understood in part because they possibly affect several neurobiological networks simultaneously. We studied the effect of the 5-HT2C receptor agonist WAY-163909 (0.3 and 3 mg/kg; i.p.) on the tissue concentration of dopamine (DA), 5-HT and noradrenaline (NA) in 29 rat brain regions related to motor, cognitive, mood and vegetative networks. We found that WAY-163909, without altering the tissue concentration of NA, increased 5-HT concentrations in the medial orbitofrontal cortex and the motor cortex M2 at 3 mg/kg and decreased it in the dorsolateral orbitofrontal cortex at 0.3 mg/kg. WAY-163909 enhanced DA concentrations in the central nucleus of the amygdala at 0.3 mg/kg and reduced it in the dorsal hypothalamus at 3 mg/kg. Using correlative analysis of the tissue content of monoamines, WAY-163909 dramatically changed the profile and the pattern of the correlations within and between monoaminergic systems without drastically changing the total number of these correlations. The profile of these changes in correlations was dose-dependent as it was very different between the two doses within and among monoaminergic systems. In conclusion, the data indicated that the 5-HT2C receptor agonist WAY-163909 quantitatively alters monoamine content in very few regions but promotes multiple changes of monoaminergic connectivity in the brain. Highlights: The 5-HT2C agonist WAY-163909 altered serotonin and dopamine tissue content in a few brain regions of the 29 studied. WAY-163909 did not modify noradrenaline tissue content. WAY-163909 disrupted monoaminergic connectivity assessed by correlations of tissue contents across the brain. The profile of correlations between 0.3 and 3 mg/kg (i.p.) WAY-163909 was very different for all monoamines.